Intervention models to solve the declining problem of swamp buffalo (Bubalus bubalis) population in Ubon Ratchathani province of Thailand - Anuwat Wiratsudakul (2018)
Swamp buffalo population in Thailand has dramatically decreased in the last three decades. The present study was conducted to predict trends and future population size of swamp buffaloes and to formulate different interventions to prevent further decline and rejuvenate the existing population. The study is based on a questionnaire survey to access information regarding buffalo husbandry and marketing. Based on derived data, age-structured Leslie matrix population model was constructed to predict the population of the buffalo cows in the coming decades. Three different intervention models were subsequently proposed including Buffalo bank campaign, prohibition of slaughtering buffalo cows and the combination of these two interventions. A total of 398 farmers rearing buffaloes were interviewed and data encompassed information on 1,366 buffaloes (418 buffalo bulls and 948 cows) were retrieved. Initial buffalo cow population in Ubon Ratchathani province was estimated to be 42,766 heads. The number was projected to decline by 36% in the next ten years, with population growth rate estimated to be 0.93. The most feasible and sustainable intervention was to carry out both campaigns simultaneously. This strategy allows the slaughtering prohibition to be successful with the support from the Buffalo bank. These campaigns should be rigorously implemented to maintain this valuable livestock resource. The present model might be implemented for similar studies in different parts of the developing world.